Major postoperative complications after pancreatic resection for P-NETS are not associated to earlier recurrence. Issue 11 (November 2017) - Valente, R.; Lykoudis, P.; Tamburrino, D.; Inama, M.; Passas, I.; Toumpanakis, C.; Luong, T.V.; Davidson, B.; Imber, C.; Malagò, M.; Rahman, S.H.; Shankar, A.; et al.
Abstract: Background: The oncological impact of surgical complications has been studied in visceral and pancreatic cancer. Aim: To investigate the impact of complications on tumour recurrence after resections for pancreatic neuroendocrine tumours. Methods: We have retrospectively analysed 105 consecutive resections performed at the Royal Free London Hospital from 1998 to 2014, and studied the long-term outcome of nil-minor (<3) versus major (≥3) Clavien–Dindo complications (CD) on disease-free (DFS) and overall survival (OS). Results: The series accounted for 41 (39%) pancreaticoduodenectomies, two (1.9%) central, 48 (45.7%) distal pancreatectomies, eight (7.6%) enucleations, four (3.8%) total pancreatectomies. Sixteen (15.2%) were extended to adjacent organs, 13 (12.3%) to minor liver resections. Postoperative complications presented in 43 (40.1%) patients; CD grade 1 or 2 in 23 (21.9%), grades ≥3 in 20 (19%). Among 25 (23.8%) pancreatic fistulas, 14 (13.3%) were grades B or C. Thirty-four (32.4%) patients developed exocrine, and 31 (29.5%) endocrine insufficiency. Seven patients died during a median 27 (0–175) months follow up. Thirty-day mortality was 0.9%. OS was 94.1% at 5 years. Thirty tumours recurred within 11.7 (0.8–141.5) months. DFS was 44% at 5 years. At univariate analysis, high-grade complications were not associated with shorter DFS (p = 0.744). At multivariate analysis, no parameter was independent predictor for DFS or OS. The comparison of nil-minor versus major complications showed no DFS difference (p = 0.253). Conclusion: From our series, major complications after P-NETs resection are not associated to different disease recurrence; hence do not require different follow up or adjuvant regimens. Abstract : Mini abstract: The oncological impact of surgical complications has been investigated in colon, oesophagus and pancreatic cancer. This is the first study addressing the question on pancreatic neuroendocrine tumours. Our retrospective analysis on 105 consecutive patients found no impact of major Clavien–Dindo complications on tumour recurrence and long term survival.